2020
DOI: 10.1002/aqc.3481
|View full text |Cite
|
Sign up to set email alerts
|

Status of aquatic and riparian biodiversity in artificial lake ecosystems with and without management for recreational fisheries: Implications for conservation

Abstract: Humanity is facing a biodiversity crisis, with freshwater‐associated biodiversity in a particularly dire state. Novel ecosystems created through human use of mineral resources, such as gravel pit lakes, can provide substitute habitats for the conservation of freshwater and riparian biodiversity. Many of these artificial ecosystems are subject to a high intensity of recreational use, however, which may limit their biodiversity potential. The species richness of several taxa (plants, amphibians, dragonflies, dam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 62 publications
0
6
0
1
Order By: Relevance
“…Yet, in previous studies in the same study area, recreational-fisheries management and stocking in gravel pit lakes did not negatively affect local species richness and the presence of threatened taxa across a wide range of riparian and aquatic taxa (e.g., dragonflies, macrophytes; Nikolaus et al, 2021). However, predation impacts on selected species of zooplankton and macrozoobenthos (not studied by Nikolaus et al, 2021) are still plausible, as the presence of fish repeatedly has been shown to shape composition, size structure and abundance of lower trophic levels in previously fish-free lake ecosystems (Knapp et al, 2001;Lemmens et al, 2015). Some taxa, such as amphibians, are particularly sensitive to fish predation and thus would benefit from fish-free waters (Leu et al, 2009;Schmidt et al, 2021).…”
Section: Con Clus Ions and Implic Ationsmentioning
confidence: 51%
“…Yet, in previous studies in the same study area, recreational-fisheries management and stocking in gravel pit lakes did not negatively affect local species richness and the presence of threatened taxa across a wide range of riparian and aquatic taxa (e.g., dragonflies, macrophytes; Nikolaus et al, 2021). However, predation impacts on selected species of zooplankton and macrozoobenthos (not studied by Nikolaus et al, 2021) are still plausible, as the presence of fish repeatedly has been shown to shape composition, size structure and abundance of lower trophic levels in previously fish-free lake ecosystems (Knapp et al, 2001;Lemmens et al, 2015). Some taxa, such as amphibians, are particularly sensitive to fish predation and thus would benefit from fish-free waters (Leu et al, 2009;Schmidt et al, 2021).…”
Section: Con Clus Ions and Implic Ationsmentioning
confidence: 51%
“…Nevertheless, repeated stocking of a limited number of species could lead to biotic homogenization of taxonomic (Matern et al, 2019, 2022; Radomski & Goeman, 1995) and functional diversity among lakes managed for fishery purposes. Fishery managers must account for this potential risk of loss of community diversity at the regional level, especially because gravel pit lakes are primarily managed for recreational fisheries, as in Central Europe (Matern et al, 2019; Nikolaus et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Aquatic vegetation coverage (both submerged and emergent) of each lake was estimated between June and August of 2016 using snorkel surveys along equidistant transects following Schaumburg et al (2014) and described in detail in Nikolaus et al (2021). Surveys were completed on equidistant sampling units surrounding the shoreline of each lake and then transformed into percent of the lake area covered by vegetation (hereafter, percent vegetation coverage).…”
Section: Methodsmentioning
confidence: 99%
“…A large gravel pit lake, Meitzer See, with a surface area of 19.5 ha, was, therefore, designated as a reference lake. This lake was not sampled for this analysis, but it was one of a full set of 16 lakes sampled for a wider project (see Höhne et al, 2020;Matern et al, 2019Matern et al, , 2022Nikolaus et al, 2021;Radinger et al, 2023). On this reference lake, 16 nets were deployed to correspond with the standards for 20 ha lakes.…”
Section: Fish Samplingmentioning
confidence: 99%